Problems of State Defense Financing Policy and Its Implications on The State Defense System in Indonesia - Asral Efendi; M. Adnan Madjid; Irdam Ahmad; Tahan Samuel Lumban Toruan (Budapest International Research and Critics University, 2022)
The dynamics of Indonesia's strategic environment on an international, regional, and national scale have raised concerns about the emergence of threats in the form of military threats, non-military threats, and hybrid threats that can weaken national defense. For this reason, sufficient national defense financing is needed, so that Indonesia has a strong national defense system. This study aims to explore the problems found in the national defense financing policy in Indonesia and its implications for the National Defense System in Indonesia from a defense economic perspective. This research is descriptive qualitative by using library data. The results of the study indicate that there are several problematic policies on state defense financing in Indonesia, that is funding for national defense is not sufficient enough, Defense's budget is still dominated by personnel expenditures, Implications for the funding of reserve components and supporting components, There is no synchronization of policies related to national defense financing, The defense financing policy has the potential to threaten the sovereignty, and finally, The perspective or paradigm that the defense budget at the Ministry of Defense is the only source of state defense financing in supporting the national defense function. This study also provides study recommendations through harmonization of laws related to the financing of state defense, to provide space for the public to participate in financing the national defense, and to develop collaborative governance in the financing of national defense.to strengthen the national defense system in the future.